2013
DOI: 10.1038/bmt.2013.177
|View full text |Cite
|
Sign up to set email alerts
|

Early peripheral blood and T-cell chimerism dynamics after umbilical cord blood transplantation supported with haploidentical cells

Abstract: Single-unit umbilical cord blood (CB) SCT is limited by low total nucleated cell (TNC) dose. Co-infusion of CD34 þ cells from a third party HLA-mismatched donor, known as dual or haplo-cord transplant, reduces the period of post-transplant neutropenia and related complications. The aim of this study was to analyze the value of early post-transplant peripheral blood (PB) and T cell chimerism after 28 dual transplants regarding CB engraftment. Cumulative incidence of myeloid engraftment at 30 days was 93% with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…This suggests that assessing chimerism before day 60 may indicate impending CGF. This is in line with that reported by the Spanish group in the haplo-cord transplant setting [42]. They found that the dynamics of UCB chimerism over time at days 14, 21, and 28 predicts for CGF, which they defined as absence of UCB-specific alleles by short tandem repeat PCR at day 30.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This suggests that assessing chimerism before day 60 may indicate impending CGF. This is in line with that reported by the Spanish group in the haplo-cord transplant setting [42]. They found that the dynamics of UCB chimerism over time at days 14, 21, and 28 predicts for CGF, which they defined as absence of UCB-specific alleles by short tandem repeat PCR at day 30.…”
Section: Discussionsupporting
confidence: 90%
“…These rates of CGF after haplo-cord HSCT appear on par to the reported rates of 4% to 20% in the myeloablative setting and 6% to 12% in the RIC setting using single and double UCB approaches, with variable graft-versus-host-disease prophylaxis [4042]. Brunstein et al [43] reported a 10% rate of CGF in a multi-institutional protocol using a RIC double UCB approach.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…On the other hand, TNC content showed influence on myeloid engraftment, only in a minority of the cases included in this analysisdthose achieving engraftment beyond day 16. This group of patients may have experienced an early CB graft dominance, which leads to a relatively lower contribution of the TPD cells, as previously described [23]. Also, HLA matching had no impact on longterm CB engraftment.…”
Section: Discussionmentioning
confidence: 66%
“…The third-party cells infused in this procedure contribute to the fast neutrophil recovery after transplantation [23]. However, the role of the third-party cells might exceed the sole function of providing a bridge engraftment.…”
Section: Discussionmentioning
confidence: 99%